TEACHING GRAMMAR THROUGH SNOWBALL THROWING TECHNIQUE IN EFL CLASSROOM - Andriani, Diyah Iis; Wahyuni, Yuli (CV. Pena Persada, 2020)
Teaching grammar had been a crucial aspect of foreign language teaching because grammatical competence is important for communication. However, learning grammar is difficult for most Indonesian students because of the monotonous techniques implemented by the teachers. Snowball throwing is one of the creative techniques in teaching grammar. Further, tense is one of the objects to learn by students in structure. Therefore, based on the description above, the aims of this study were to describe the implementation of snowball throwing technique in teaching grammar, the students’ response towards the implementation of the snowball throwing technique, and the benefits of applying the technique. The method applied in conducting this study was descriptive qualitative analysis. Particularly, the participants of this study were 100 first semester students of English department in Universitas Pamulang taking the subject of Basic Grammar. In order to support the study finding, the writers taught grammar using snowball throwing technique, and the participants were selected based on the purposive sampling. The data were achieved from classroom observation and students’ interview through questionnaire. Further, the findings showed that there were nine stages in implementing snowball throwing in teaching grammar. The stages consisted of preparing teaching material, forming group, explaining the material to the leader of the group, re-explaining the material to the members of the group, formulating question, tossing the ball, answering questions, evaluating teaching and learning process, and giving conclusion. After finishing the learning, the writers distributed the questionnaire. These instruments were administered to analyse and obtain the findings of study. Practically, the writers expected that the study will enrich the benefits of snowball throwing technique in learning grammar, such as improving students’ comprehension in learning grammar, creating enjoyable learning atmosphere, developing students’ cooperation skill, and increasing students’ participation in the class.